1978
DOI: 10.1111/j.1432-1033.1978.tb12330.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Microtubule Proteins to DNA: Specificity of the Interaction

Abstract: Tubulin is detected among the DNA-binding proteins when an extract from fibroblasts is chromatographed on DNA-cellulose. Further purification of the colchicine-binding activity shows that purified tubulin from fibroblasts does not bind to DNA. Depolymerized brain microtubule proteins show a high affinity for DNA. The fraction bound is composed of tubulin and microtubule-associated proteins. Experiments with fractionated microtubule proteins indicate that tubulin-free microtubuleassociated proteins bind to DNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Considering the relationship between the DNA and RNA, this finding also suggested a possible interaction between tau and the DNA. Indeed, Corces et al showed that brain depolymerised microtubule-associated proteins bind the DNA with high affinity [ 70 ]. Using an in vitro assay, Corces et al further showed that DNA inhibits microtubule assembly in a concentration-dependent manner, indicating that microtubule-associated proteins have more affinity to the DNA than to the microtubules [ 71 ].…”
Section: Nuclear Tau and Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the relationship between the DNA and RNA, this finding also suggested a possible interaction between tau and the DNA. Indeed, Corces et al showed that brain depolymerised microtubule-associated proteins bind the DNA with high affinity [ 70 ]. Using an in vitro assay, Corces et al further showed that DNA inhibits microtubule assembly in a concentration-dependent manner, indicating that microtubule-associated proteins have more affinity to the DNA than to the microtubules [ 71 ].…”
Section: Nuclear Tau and Alzheimer’s Diseasementioning
confidence: 99%
“…The capacity of tau to interact with nucleic acids, such as the RNA and DNA [ 68 , 69 , 70 , 71 ], and raise the melting temperature of the DNA suggests it could also play a role in DNA protection [ 72 ] ( Figure 3 ). In vitro evidence showed that tau could protect the dsDNA from thermal denaturation and enhance its renaturation [ 78 ].…”
Section: Nuclear Tau and Alzheimer’s Diseasementioning
confidence: 99%
“…Although Tau protein hyperphosphorylation and aggregation are hallmarks associated with the progress of the disease [16], recent studies point to a nuclear origin of AD, whereby nuclear Tau [17,18], and NL proteins [19,20] would play a decisive role. Tau interacts with DNA [21][22][23], including heterochromatin contacts [24,25], genome protection [26][27][28][29] by modulating euchromatin gene expression [30,31] and it accumulates in cell nuclei throughout neuronal aging [32]. AD onset and progression takes place in parallel with the gradual disappearance of Tau from neuronal nuclei and its accumulation in the cytoplasm [17].…”
Section: Introductionmentioning
confidence: 99%
“…Since DNA binds to MAPs, but not to tubulin [26], we suggest that the presence of MAPS facilitates the zinc-tubulin oligomers formation. Depletion of MAPS results in longer and wider tubulin-sheets.…”
Section: Influence Of Maps In Length and Width Of Sheetsmentioning
confidence: 94%